Networks and competitive advantage: Spontaneous vs. induced clusters - Kavadarlı, Altın. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
The cluster concept, described as the geographical concentration of interconnected organizations, has received much attention in the field of strategic management. Porter’s (1998) diamond model suggests that clusters positively impact competitive advantage, since the proximity of businesses, customers, and suppliers urges all the firms to innovate and upgrade, so that productivity, innovation, and new business formation is increased. This qualitative study aims to analyze the network structures among firms in spontaneous vs. induced clusters based on the case studies of two types of hosiery clusters in different geographical locations in Istanbul (where most of the producers are located), one located in Ikitelli Industrial Zone (induced cluster) and the other located in Yesildirek district (spontaneous cluster). In-depth, semistructured, face-to-face interviews were held with hosiery firms in the two cluster types in order to get a holistic understanding of the present network structures as well as to explain how these network ties are potential sources of competitive advantage. The results supported the main hypothesis, as networks were found to be more intense in the spontaneous cluster relative to the induced cluster. Although located in the same cluster, the firms in the induced cluster did not develop close relationships with the other firms, therefore inter-firm relations can be described as weakly mutually dependent, or arm’s length in terms of Uzzi (1997). On the other hand, the existence of dense inter-firm networks, high level of cooperation, mutual-trust, knowledge-sharing, embedded and long-term relations among the firms in the Yesildirek spontaneous cluster has formed a solid base of support and trust.
Keywords: Management information systems.; Electric networks, Active.